Irrigation-nutrition linkages: Evidence from northern Ghana - Mekonnen, Dawit Kelemework; Choufani, Jowel; Bryan, Elizabeth; Abizari, Abdul-Razak; Ringler, Claudia; Amikuzuno, Joseph (International Food Policy Research Institute, 2019)
We analyze the linkages between irrigation and nutrition using data from irrigators and non-irrigators in Northern Ghana. The results show that (i) there is a modest difference in the overall household dietary diversity score between irrigators and non-irrigators, (ii) there are significant differences in the consumption of animal source foods between irrigators and non-irrigators, (iii) there are significant differences in the consumption of fruits and vegetables as well as sugar and honey between irrigators and non-irrigators, and (iv) the sources of food consumption differ between irrigators and non-irrigators. The analysis shows strong association between households’ nutritional status and their access to irrigation, with evidences suggesting that the irrigation-nutrition linkages play out both through the income and production pathways in Northern Ghana.